Combining deterministic and probabilistic matching to reduce data linkage errors in hospital administrative data. (2017) - Hagger-Johnson, Gareth; Harron, Katie; Aldridge, Rob; Fu, Bo; Setakis, Efrosini; Goldstein, Harvey; Gilbert, Ruth
No abstract available